Evaluating cetacean body condition; a review of traditional approaches and new developments. Issue 12 (13th May 2020) - Castrillon, Juliana; Bengtson Nash, Susan
Abstract: The ability to accurately gauge the body condition of free‐swimming cetaceans is invaluable in population and conservation biology, due to the direct implications that this measure has on individual fitness, survival, and reproductive success. Furthermore, monitoring temporal change in body condition offers insight into foraging success over time, and therefore the health of the supporting ecosystem, as well as a species' resilience. These parameters are particularly relevant in the context of widespread and accelerated, climate‐induced habitat change. There are, however, significant logistical challenges involved with research and monitoring of large cetaceans, which often preclude direct measure of body condition of live individuals. Consequently, a wide variety of indirect approaches, or proxies, for estimating energetic stores have been proposed over past decades. To date, no single, standardized, approach has been shown to serve as a robust estimation of body condition across species, age categories, and in both live and dead individuals. Nonetheless, it is clear that streamlining and advancing body condition measures would carry significant benefits for diverse areas of cetacean research and management. Here, we review traditional approaches and new applications for the evaluation of cetacean energetic reserves. Specific attention is given to the criteria of measure performance (sensitivity and accuracy), level of invasiveness, cost and effort required for implementation, as well as versatility e.g. applicability across different species, age groups, as well as living versus deceased animals. Measures have been benchmarked against these criteria in an effort to identify key candidates for further development, and key research priorities in the field. Abstract : Body condition in cetaceans has a direct implication on individual fitness, survival, and reproductive success, offering insight into their foraging success over time, and therefore the health of the supporting ecosystem and species resilience. However, to date, no single, standardized approach has been shown to be a robust estimation of body condition across species or age categories in both live and dead individuals. We review the traditional approaches and new developments for measuring energetic health in cetaceans, focusing in how versatile these approaches are across species, age, and life categories. In addition, this review will identify the capacity for high throughput analysis, which is necessary for application in routine monitoring.